2004
DOI: 10.1179/030192304225018244
|View full text |Cite
|
Sign up to set email alerts
|

Ladle glaze: major source of oxide inclusions during ladle treatment of steel

Abstract: It was found in the samples taken at and below the slag line that a slag infiltrated layer was covered by an outer layer containing many MgO 'islands' of various sizes. The microstructure of the infiltrating slag was the same as the matrix of the outer layer. The slag was found to decompose into the compound 3CaO.Al 2 O 3 and a liquid phase during the cooling process. The former phase along with tiny MgO particles from the ladle glaze was found to be one of the major sources of inclusions during the degassing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 12 publications
2
68
1
1
Order By: Relevance
“…The feasibility of the physical detachment can be supported by the microstructure of the glaze layer showing the existence of spinel particles on the interface of glaze and molten steel. Several previous studies [7][8][9][10][11] for the ladle glaze of a magnesite lining also suggested that the particles like MgO originally formed in the glaze layer can be retained in the liquid steel as inclusions. For example, Beskow and Du Sichen 10) reported that the complex inclusion of liquid CaO-Al 2 O 3 (-MgO-SiO 2 ) bearing MgO particles, one of the typical inclusions in a practical ladle treatment, was most probably originated from the ladle glaze itself.…”
Section: Molten Steel and Inclusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The feasibility of the physical detachment can be supported by the microstructure of the glaze layer showing the existence of spinel particles on the interface of glaze and molten steel. Several previous studies [7][8][9][10][11] for the ladle glaze of a magnesite lining also suggested that the particles like MgO originally formed in the glaze layer can be retained in the liquid steel as inclusions. For example, Beskow and Du Sichen 10) reported that the complex inclusion of liquid CaO-Al 2 O 3 (-MgO-SiO 2 ) bearing MgO particles, one of the typical inclusions in a practical ladle treatment, was most probably originated from the ladle glaze itself.…”
Section: Molten Steel and Inclusionsmentioning
confidence: 99%
“…Recently, Beskow and Du Sichen 10) studied the formation of ladle glaze and its influence on the generation of nonmetallic inclusions in a practical ladle treatment. The ladle lining (refractory) in their study was magnesite refractory (carbon-bearing MgO lining).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14) Spinel inclusions have been thought to be hard, irregular and nondeformable, and it is commonly very harmful to the final products.…”
Section: Effect Of Mg Addition On the Evolution Of Inclusions In Al-cmentioning
confidence: 99%
“…Calcium aluminate inclusions are usually globular with low melting points, so performing calcium treatment is very common in steelworks in order to have such inclusions, but there is still lack of agreement about the harmness of these inclusions. Spinel and calcium aluminate inclusions are mainly found in Al-killed steel, [4][5][6] and many scholars have contributed to research the formation and evolution mechanism of these inclusions, such as Itoh el al., 7,8) Park et al, [9][10][11] Kang et al, 12) Seo et al 13) and Wang et al 5,6,[14][15][16] The proposed mechanism was commonly mentioned that the dissolved Mg and Ca were supplied from the slag and refractory, and the MgO-Al2O3 system inclusions formed by the reaction between alumina inclusions and dissolved Mg. Besides, Kang et al 12) and Wang et al 6,[14][15][16] indicated that MgO-Al2O3 system was not stable when there was a trace of dissolved Ca, would transfer into CaO-MgO-Al2O3 system.…”
Section: Introductionmentioning
confidence: 99%